Review of the genus Scaeosopha Meyrick, 1914 (Lepidoptera, Cosmopterigidae, Scaeosophinae) in the world, with descriptions of sixteen new species - Li, Houhun; Zhang, Zhiwei; Sinev, Sergey Yu. (Zootaxa, 2012)
The genus Scaeosopha Meyrick is reviewed on a worldwide basis. A total of 26 species are treated, which are divided intotwo species groups except S. atrinervis Meyrick, 1931, the percnaula-group and the mitescens-group. Sixteen new speciesare described: S. betrokensis Sinev et Li sp. nov., S. erecta Li et Zhang sp. nov., S. hongkongensis Li et Zhang sp. nov.,S. minuta Sinev et Li sp. nov., S. nullivalvella Li et Zhang sp. nov., S. sabahensis Sinev et Li sp. nov., S. spinivalvata Liet Zhang sp. nov., S. tuberculata Li et Zhang sp. nov., S. victoriensis Sinev et Li sp. nov., S. convexa Li et Zhang sp. nov.,S. dentivalvula Li et Zhang sp. nov., S. gibbosa Li et Zhang sp. nov., S. grandannulata Li et Zhang sp. nov., S. nigrimar-ginata Li et Zhang sp. nov., S. rarimaculata Li et Zhang sp. nov. and S. trigonia Li et Zhang sp. nov. One new synonymis established: Scaeosopha stagnigera Meyrick, 1932 syn. nov. (= Scaeosopha percnaula Meyrick, 1914), and one newcombination is proposed: Scaeosopha triocellata (Stainton, 1859) comb. nov. The previously unknown females of S.chionoscia Meyrick, 1933, S. sinevi Ponomarenko et Park, 1997 and S. sattleri Li, 2005 are described for the first time.Photographs of the adults and the genitalia of the new species as well as several of the described species are provided, along with a key for the identification of the known species and two maps to show the distribution of these species.